Complex thinking through a Transition Design-guided Ideathon: testing an AI platform on the topic of sharing economy - Sanabria-Z, Jorge; Castillo-Martínez, Isolda Margarita; González-Pérez, Laura Icela; Ramírez-Montoya, María Soledad (Frontiers in Education, 2023)
Rationale The development of the complex thinking meta-competency in the education of university students potentially promotes high capacities, where artificial intelligence (AI) might work as a supporting structure. Objective This proof-of-concept study of an AI-based platform aimed to integrate a sequence of activities into the design of an online platform to assess the development of complex thinking competency in higher education students. Method The Transition Design method was used within an Ideathon event supported by an AI platform to provide students with a sharing economy challenge. A total of 31 university students from five university campuses in Mexico synchronously participated. An instrument was applied in the pre-test and post-test phases to explore the complex thinking meta-competency and its sub-competencies of critical, innovative, scientific, and systemic thinking. Results Two hypotheses were tested, both of which turned out to be true: (a) the functioning of the constructed learning situation and (b) the model of the learning situation. Conclusion These findings may be of value to scientific and academic communities, as well as social and business organizations interested in developing high capacities of complex thinking and educational innovations using digital platforms.